2009
DOI: 10.1002/bmc.1301
|View full text |Cite
|
Sign up to set email alerts
|

Residue analysis of kresoxim‐methyl and boscalid in fruits, vegetables and soil using liquid–liquid extraction and gas chromatography–mass spectrometry

Abstract: A GC-MS procedure for simultaneously determining and validating kresoxim-methyl and boscalid has been developed in fruit, vegetable and soil matrices. The method was based on one-step liquid-liquid extraction with acetone and dichloromethane solvents. Estimated limits of detection (LODs) for kresoxim-methyl and boscalid were 0.006 and 0.015 mg/kg, and limits of quantification (LOQs) were 0.02 and 0.05 mg/kg, respectively. The intra- and inter- precision were achieved with RSD better than 13.8 and 14.5%, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Soil contamination has also been assessed in different agricultural areas in different countries throughout the world (Belmonte Vega et al, 2005;Gonçalves and Alpendurada, 2005;Lazartigues et al, 2011;Liu et al, 2010;Park et al, 2011;Smalling and Kuivila, 2008), with the pesticides most often found being organochlorines, organophosphates, carbamates, triazines, ureas or triazoles. Their concentration and effects have generally been determined from a toxicological perspective, or with a view to developing a suitable methodology for analyzing pesticide residues.…”
mentioning
confidence: 99%
“…Soil contamination has also been assessed in different agricultural areas in different countries throughout the world (Belmonte Vega et al, 2005;Gonçalves and Alpendurada, 2005;Lazartigues et al, 2011;Liu et al, 2010;Park et al, 2011;Smalling and Kuivila, 2008), with the pesticides most often found being organochlorines, organophosphates, carbamates, triazines, ureas or triazoles. Their concentration and effects have generally been determined from a toxicological perspective, or with a view to developing a suitable methodology for analyzing pesticide residues.…”
mentioning
confidence: 99%
“…Grape ( Vitis vinifera ) is an important commercial crop planted widely around the world. However, parasites such as gray mold Liu, Dong, et al (), Liu, Guo, et al, (), powdery mildew (Vaquero‐Fernández et al, ) and downy mildew (Angioni et al, ) have a strong impact on grape yield and quality. Therefore, it is necessary to use fungicides to control fungus during grape growth.…”
Section: Introductionmentioning
confidence: 99%
“…Many analytical methods have been introduced to detect boscalid and fludioxonil, including high‐performance liquid chromatography (HPLC) (Vaquero‐Fernández et al, ), liquid chromatography–tandem mass spectrometry (LC–MS/MS) (Hiemstra & De Kok, ; Kovacova et al, ), gas chromatography (GC) (Ko et al, ; Munitz, Resnik, & Montti, ; Zhang et al, ) and gas chromatography–tandem mass spectrometry (GC–MS) Liu, Dong, et al, (), Liu, Guo, et al, (); (Rodrígurz‐Cabo, Rodríguez, Ramil, & Cela, ; Angioni et al, ; Čuš, Bach, Barnavon, & Pongrac, ). For example, Vaquero‐Fernández et al () analyzed the residue of fludioxonil in wine by HPLC, with average recoveries of 97.00–99.50% and relative standard deviations (RSDs) of <10%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BL can be extracted from the sample by alternative methodologies, though they are mostly based on the use of high amounts of organic solvents. Acetone has been employed to effectively extract BL and other pesticides from different fruit and vegetable matrices, followed by a clean-up step based on liquid-liquid extraction with dichloromethane (Hiemstra & de Kok, 2007;Liu, Dong, Qin, & Zheng, 2010). For multi-residue analysis, the QuEChERS (Quick Easy, Cheap, Effective, Rugged, and Safe) methodology, which employs acetonitrile to extract pesticides together with a clean-up of the extract based on solid-phase extraction with primary-secondary amine (Lehotay, 2007), or with C 18 or graphitized carbon black phases (Walorczyk, 2008;Walorczyk & Gnusowski, 2009), is widely used and it has been broadly validated.…”
Section: Introductionmentioning
confidence: 99%